Professional training of future specialists in tourism studies in Ukraine under conditions of integration in European educational space - Beskorovaynaya, Larisa (ScienceRise: Pedagogical Education, 2017)
In the article the author made a theoretical analysis of the European system of professional training for future masters within the tourism industry. The analysis was focused on the conceptual framework of professional training, the principles of training, and agreed teaching methodology. The article also analyzed the basic level of documentation required for the relevant standards with which the education system for the future masters of tourism should be based. The author stated that when deciding the importance of the theoretical analysis of international experience on their training within the tourism field, it should be determined by its importance within the global education system. Analysis of research into the training of future masters of tourism within higher education showed that currently most importance is given to the practical part of this process. Proven as timeliness and importance of the research European integration to the national system of higher education in Ukraine. By optimizing the considered areas of modern Ukrainian system of training future master in tourism in accordance with international and European educational systems. The study identified some ways to integrate the Ukrainian higher education system into the European model. The author also proposed a number of ways to improve the entry of Ukrainian education and science into a single joint educational and research area. In the article the author suggested a number of promising areas for further research themes